(untitled) - Berrett, Lisa (Lincolnwood, Ill, 1996)
A selection of Mother Goose rhymes, including "Little Tom Tucker," "Hickory, Dickory, Dock," and "Georgie Porgie."
Includes index.
Keywords: Nursery rhymes; Children's poetry